Comparing Information Diffusion Structure in Weblogs and Microblogs - Yang, Jiang; Counts, Scott (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
To better understand and characterize the emerging social medium of microblogging we conducted a comparison between Twitter and a weblog network for their respective information diffusion structures. We found systematic differences between the two social media in their contribution, navigation, and interactive structural patterns. Findings revealed the unique role and characteristics of microblogs in the social media design space. Implications are discussed.